Does genetic distance between parental species influence outcomes of hybridization among coral reef butterflyfishes?. Issue 11 (16th May 2014) - Montanari, Stefano R.; Hobbs, Jean‐Paul A.; Pratchett, Morgan S.; Bay, Line K.; Van Herwerden, Lynne
Abstract Christmas Island is located at the overlap of the Indian and Pacific Ocean marine provinces and is a hot spot for marine hybridization. Here, we evaluate the ecological framework and genetic consequences of hybridization between butterflyfishes Chaetodon guttatissimus and Chaetodon punctatofasciatus. Further, we compare our current findings to those from a previous study of hybridization between Chaetodon trifasciatus and Chaetodon lunulatus. For both species groups, habitat and dietary overlap between parental species facilitate frequent heterospecific encounters. Low abundance of potential mates promotes heterospecific pair formation and the breakdown of assortative mating. Despite similarities in ecological frameworks, the population genetic signatures of hybridization differ between the species groups. Mitochondrial and nuclear data from C. guttatissimus × C. punctatofasciatus (1% divergence at cyt b) show bidirectional maternal contributions and relatively high levels of introgression, both inside and outside the Christmas Island hybrid zone. In contrast, C. trifasciatus × C. lunulatus (5% cyt b divergence) exhibit unidirectional mitochondrial inheritance and almost no introgression. Back‐crossing of hybrid C. guttatissimus × C. punctatofasciatus and parental genotypes may eventually confound species‐specific signals within the hybrid zone. In contrast, hybrids of C. trifasciatus and C. lunulatus may coexist with and remain genetically distinct from the parents. Our results, and comparisons with hybridization studies in other reef fish families, indicate that genetic distance between hybridizing species may be a factor influencing outcomes of hybridization in reef fish, which is consistent with predictions from terrestrially derived hybridization theory.